The fibronectin adhesin of Candida albicans. - Klotz, S A (1994)
Candida albicans possesses on its cell surface an adhesin which binds the whole viable fungus to subendothelial extracellular matrix and matrix proteins. The adhesin is composed of 75 to 80% carbohydrate and approximately 20 to 25% protein by weight. High-performance liquid chromatography of material eluted from a fibronectin-agarose affinity column demonstrates the presence of three peaks, all of which on sodium dodecyl sulfate-polyacrylamide gel electrophoresis show the presence of one protein of approximately 60 kDa. Molecular weight sizing column chromatography, however, demonstrates that the adhesin elutes with an apparent molecular mass of 42 kDa. The N terminus of the 60-kDa glycoprotein is blocked to Edman degradation. The fibronectin adhesin of C. albicans is a glycoprotein that may be present and functional as an aggregate or multimer of a 60-kDa protein.